2023
DOI: 10.1007/s40710-023-00624-z
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Yield and Water Productivity of Tomato as Influenced by Deficit Irrigation Water Management

Abstract: The deficit irrigation offers water savings potential that is becoming popular in arid and semi-arid regions reducing freshwater use over time. A two-year factorial experiment was conducted to evaluate growth, yield and water productivity of tomato under water deficit irrigation of the drip and furrow method. The experiment was carried out in a split-plot design with drip irrigation and furrow irrigation as main plot treatments, and soil moisture regimes (0, -10, -20, -30 kPa) as subplots. Data were collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 69 publications
1
12
0
Order By: Relevance
“…The AquaCrop model overestimate at the application of FI application and the performance value were poor at high deficit irrigation application. The study conforms to the work of [15,24,28,46], who suggests the AquaCrop performance decreases as the application of irrigation depth decreases. The performance of the AquaCrop varies crop to crop and cultivars.…”
Section: Statically Validation Performance Of Aquacropsupporting
confidence: 88%
See 2 more Smart Citations
“…The AquaCrop model overestimate at the application of FI application and the performance value were poor at high deficit irrigation application. The study conforms to the work of [15,24,28,46], who suggests the AquaCrop performance decreases as the application of irrigation depth decreases. The performance of the AquaCrop varies crop to crop and cultivars.…”
Section: Statically Validation Performance Of Aquacropsupporting
confidence: 88%
“…The above results were due to the reason that AquaCrop clarifies the process of canopy cover decrease at crop senescence [25,26]. It also supported by Mukherjee et al [46] suggested that the level of plant water stress affected the model performance.…”
Section: Statically Validation Performance Of Aquacropmentioning
confidence: 59%
See 1 more Smart Citation
“…However, compared to the terrestrial herb diversity, the aquatic habitat demonstrated lower diversity, with Simpson Index values ranging from 0.45 to 0.63 and Shannon-Wiener Index values from 0.6 to 1.04. The presence of speci c species during certain seasons suggests the adaptability of the ecosystem to seasonal variations (Mukherjee et al, 2023). A noteworthy observation was a reduction in both species' diversity and the total number of species, in the aquatic habitats.…”
Section: )mentioning
confidence: 99%
“…The effectiveness of water-saving techniques may vary depending on seasonal weather conditions, cultivation site, genotype, fertilization management, and the timing of deficit induction [17][18][19][20]. In Mediterranean and semi-arid environments, DI and RDI would save water resources and increase water productivity [21]. Studies have shown that the controlled reduction of irrigation volumes after the flowering phase of tomatoes improves fruit quality, although production may be reduced [17].…”
Section: Introductionmentioning
confidence: 99%